CONCILIATION COMMISSION AS AN OUT-OF-COURT WAY FOR LABOR DISPUTES RESOLUTION - Shaizadaev, Бахытбек Абдигалимович; Kopzhassarova, Сагынгуль Избасаровна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The Labor Code of the Republic of Kazakhstan adopted in 2015 establishes the rules governing the procedure for consideration and resolution of labor disputes, considers the protection of labor rights as the main goal and principle of labor legislation. In accordance with the legislation of the Republic of Kazakhstan, in the event of a labor dispute between the parties, two ways of protecting labor rights are provided: judicial protection of labor rights and protection of labor rights by non-judicial means. Currently, there are several ways to resolve out-of-court labor disputes between an employer and an employee. In accordance with the Labor Code of the Republic of Kazakhstan, an employee has the right to protect their rights and interests in all ways that do not contradict the law. The Conciliation Commission is a permanent body that considers an individual labor dispute between an employer and an employee, and a mandatory pre-trial stage. The article considers the historical stages of the formation and approval of the institute of the conciliation commission in the domestic legislation, the differences between the institute of the conciliation commission in the old and new versions of the Labor Code. In accordance with the latest changes made to the Labor Code, the creation of a voting commission was fixed by the employer's responsibility. In this regard, as a comparative analysis, examples from foreign experience were also given. The opinions of various authors on the advantages and disadvantages of the conciliation commission are considered. In practice, there are often cases when in the case of labor disputes, the parties go to court immediately, without observing the mandatory pre-trial stage, leaving the case without consideration and returning the claim. In this regard, it was proposed to bring employers to administrative responsibility for not creating a conciliation commission